Manajemen Risiko Proses Produksi Gula dengan Metode Failure Mode Effect and Analysis - Mila Faila Sufa; Umi Khoiriyah (Performa: Media Ilmiah Teknik Industri, 2017)
A company should pay attention to operational risk to maximise its efficiency and effectivity.Identification of failure and the cause and the impact of the failure at milling station is needed to be done so that the sugar production process can run well. Here, we employ a failure mode and effect analysis to identify the failure and its effect. We obtain 22 operational risks with two critical risks. The two critical risks are then used as top event in analysing the cause of the failure. The result from fault tree analysis shows that there are 4 basic events, which are the turbine vibrates, schedule part’s change before failure, high rainfall and the schedule and priority of processing